La topographie des monastères carolingiens à travers le Commentaire sur la Règle de saint Benoît par le maître Hildemar (vers 845-850) - Pierre Gillon (Bulletin du Centre d’Études Médiévales d’Auxerre)
The author extracts from the Commentary on the Rule of Saint Benedict, taught by the monk Hildemar, the main elements concerning the topography of monasteries : site, capacity, enclosure, hostelries, infirmary, enclosure for novices, church, cloister, chapter house, dormitory, refectory, kitchen, door, stove, etc. The data concerning the different enclosures of the monastery and the claustra monasterii bring elements to the debate on the Carolingian cloister and its porticos.